Pointwise Multipliers of Orlicz-Morrey Spaces - Ifronika, Ifronika; Hakim, Denny Ivanal; Budhi, Wono Setya (Journal of the Indonesian Mathematical Society, 2025)
We investigate the space of pointwise multipliers of Orlicz-Morrey spaces. Using the H\"older inequality in Orlicz-Morrey spaces, we prove that the space of pointwise multipliers of Orlicz-Morrey spaces contains an Orlicz-Morrey space. We also prove a partial reverse inclusion of this result. In addition, we des\-cribe the space of pointwise multipliers of Orlicz-Morrey spaces by adding some growth conditions on Young functions. Our results can be viewed as an extension of the results on pointwise multipliers of Morrey spaces.